2018
DOI: 10.36877/pmmb.a0000004
|View full text |Cite
|
Sign up to set email alerts
|

Complete genome of mangrove-derived anti-MRSA streptomycete, Streptomyces pluripotens MUSC 135T

Abstract: Microorganisms serve as attractive resources, owing to their ability to synthesize structurally-diverse substanceswith various bioactivities. Within the Bacteria domain, members of the genus Streptomyces have demonstrated remarkableability to produce clinically useful, secondary metabolites such as anticancer, antioxidants, antivirals and antibacterials.Streptomyces pluripotens MUSC 135T was isolated as novel strain from mangrove forest in Malaysia. This strain exhibitedbroad spectrum bacteriocin again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Studies demonstrated that radical scavengers like vitamin E, in the form of tocopherol and tocotrienol, can protect the glutamate-injured cells from oxidative stress. Other than vitamin E, other sources such as microbial resources were also demonstrating strong antioxidants [116][117][118][119][120][121][122][123][124][125][126] and neuroprotective properties [127][128][129][130][131][132] such as metal chelating and radical scavenging potentials [133][134][135][136][137][138][139][140] . In conclusion, neuronal cell seemed to be the most vulnerable brain cells toward glutamate toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Studies demonstrated that radical scavengers like vitamin E, in the form of tocopherol and tocotrienol, can protect the glutamate-injured cells from oxidative stress. Other than vitamin E, other sources such as microbial resources were also demonstrating strong antioxidants [116][117][118][119][120][121][122][123][124][125][126] and neuroprotective properties [127][128][129][130][131][132] such as metal chelating and radical scavenging potentials [133][134][135][136][137][138][139][140] . In conclusion, neuronal cell seemed to be the most vulnerable brain cells toward glutamate toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Streptomyces bacteria are uniquely complex microorganisms, primarily well-known as prolific producers of secondary metabolites with bioactivities such as antimicrobial, anticancer, antioxidant, and immunosuppressive activities [19,20,23,24] . Production of secondary metabolites is not essential for bacterial growth, but it is crucial to facilitate the defence mechanisms of the hosts as to ensure survival during unfavourable environmental conditions [6] .…”
Section: Unique Features Of Streptomycesmentioning
confidence: 99%
“…Mangrove ecosystem is a unique ecological niche which contains highly productive and diverse microbial community [201][202][203][204] . Similarly, the mangrove environment has been known to be potent reservoir for isolation of antibiotic-producing Actinobacteria [205] . Eccleston et al (2008) [206] revealed that the ecology has great impact on the diversity of Actinobacteria.…”
Section: Mangrove Environmentmentioning
confidence: 99%